Latin American Foreign Debt in Times of Pandemic - Natteri Romero, Iván Adolfo (2020)
The problem of Latin American foreign debt becomes an instrument of destruction of life. In this investigation we will highlight its causes and projections, we will ask about the subject who must respond to said abuse and, we will present some clues to save the situation in a context never seen before: that of the coronavirus.